2017
DOI: 10.1002/eat.22799
|View full text |Cite
|
Sign up to set email alerts
|

Stress is associated with exercise differently among individuals with higher and lower eating disorder symptoms: An ecological momentary assessment study

Abstract: Objective Stress is associated with the maintenance of eating disorders and exercise behaviors. However, it is unclear how stress is associated with exercise and vice-versa among individuals with higher levels of eating disorder symptoms in daily life. The current study tested the moderating effect of eating disorder symptoms on the relationships between: (1) daily stress and later exercise behavior and (2) daily exercise behavior and later stress. Method Female college students [N = 129, mean age = 19.19 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Prompts occurred randomly between 9:00 AM and 9:30 PM, and were at least two hours apart. Prompts not answered within 75 min of receipt counted as missing data, a standard that has been used in prior EMA studies [38].…”
Section: Ema Measuresmentioning
confidence: 99%
“…Prompts occurred randomly between 9:00 AM and 9:30 PM, and were at least two hours apart. Prompts not answered within 75 min of receipt counted as missing data, a standard that has been used in prior EMA studies [38].…”
Section: Ema Measuresmentioning
confidence: 99%
“…These few findings are in line with community‐based EMA studies, indicating that higher daily physical activity in young adults is associated with less negative affect at the end of day (Haas, Schmid, Stadler, Reuter, & Gawrilow, ) and momentary physical activity is associated with subsequent increases in positive affect within 15 min (Schwerdtfeger, Eberhardt, & Chmitorz, ). Evidence for a decrease in momentary negative affect after physical activity is considered inconclusive for community‐based samples (Liao, Shonkoff, & Dunton, 2015; Schwerdtfeger et al, ), and stress is only associated with exercise in individuals with lower levels of eating disorder symptoms (Sala, Brosof, Rosenfield, Fernandez, & Levinson, ). Furthermore, states of momentary positive and in some studies also negative affect are associated with subsequent increases in physical activity (Liao, Shonkoff, & Dunton, ; Schwerdtfeger, Eberhardt, Chmitorz, & Schaller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological Momentary Assessment (EMA) is an assessment approach that allows collecting information about sampling subjects' experiences and behaviors in real-time (or closer to real-time) in their natural environment (Shiffman et al, 2008). Ecological Momentary Assessment approach, compared to retrospective methods, provides multiple advantages such as collecting real-time information about subjects' habits and behaviors from their context (Hicks et al, 2010) or allowing to explore antecedents and consequences after individuals' behaviors appearance (Sala et al, 2017). Consequently, an EMA approach deals with some of the limitations of traditional retrospective methods' such as inaccurate subjects' retrospective answers due to their autobiographical memory biases (Schwarz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological momentary assessment approach has been also incorporated to sport psychology research and recent times have shown several studies using such an approach to assess different variables. For instance, Sala et al ( 2017 ) carried out a study analyzing the relationships between daily stress and exercise behaviors in female undergraduate students gathering subjects' exercise behaviors and affective responses to exercise using handheld electronic diaries. Williams et al ( 2016 ) studied the mediation effects of affective responses to exercise on exercise adherence.…”
Section: Introductionmentioning
confidence: 99%